A large increase in U.S. methane emissions over the past decade inferred from satellite data and surface observations. Issue 5 (2nd March 2016) - Turner, A. J.; Jacob, D. J.; Benmergui, J.; Wofsy, S. C.; Maasakkers, J. D.; Butz, A.; Hasekamp, O.; Biraud, S. C.
Abstract: The global burden of atmospheric methane has been increasing over the past decade, but the causes are not well understood. National inventory estimates from the U.S. Environmental Protection Agency indicate no significant trend in U.S. anthropogenic methane emissions from 2002 to present. Here we use satellite retrievals and surface observations of atmospheric methane to suggest that U.S. methane emissions have increased by more than 30% over the 2002–2014 period. The trend is largest in the central part of the country, but we cannot readily attribute it to any specific source type. This large increase in U.S. methane emissions could account for 30–60% of the global growth of atmospheric methane seen in the past decade. Key Points: We identify a large increase in U.S. methane emissions over the past decade Increase occurred during a time when emission inventories indicate no change in U.S. emissions The U.S. could account for 30‐60% of the global increase in atmospheric methane over the past decade